2009
DOI: 10.1007/s12262-009-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy for hydrocele revisited: a prospective randomised study

Abstract: Five percent phenol is a better sclerosant than 1% polidocanol and is as efficacious as operative treatment, with lesser morbidity and similar safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Furthermore, the rate of SES in the group without AAAM was comparable to previous findings . In randomised studies, complications included oedema, haematoma and infections were seen in 5–10% of the patients and similarly so in other studies using polidocanol and doxycycline . In none of these studies was SES studied or mentioned, but pain was reported to occur in 9–70% of the cases .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the rate of SES in the group without AAAM was comparable to previous findings . In randomised studies, complications included oedema, haematoma and infections were seen in 5–10% of the patients and similarly so in other studies using polidocanol and doxycycline . In none of these studies was SES studied or mentioned, but pain was reported to occur in 9–70% of the cases .…”
Section: Discussionsupporting
confidence: 84%
“…Cure after one treatment was also more common in patients with smaller coele, as noted previously by others . The definition of smaller coele differed between different studies, and the size of the coele (i.e., emptied volume) was not accounted for in many analyses, making comparison between studies difficult .…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, Fuse et al [18] reported none of their 15 patients to be having bilateral involvement. Agrawal et al [19] also did not report a single case with bilateral involvement. It is difficult to comment whether all these studies had selected patients with unilateral involvement only, as these studies were comparative studies, and hence, in order to rule out any confounding effect, they might have excluded the bilateral involvement.…”
Section: Discussionmentioning
confidence: 95%
“…Each agent reports a cure rate ranging from 85% to 97%, with complication rates of up to 50%. [8][9][10][11][12] Alcohol is a sclerosing agent that has a chemical irritant effect on the contacting tissue. The necrosis produced by alcohol injection is secondary to cellular dehydration, cell membrane lysis, and protein denaturation.…”
Section: Discussionmentioning
confidence: 99%